A comparison of the effects of AI‐based chatbots and peer interactions on speaking anxiety among EFL learners - Meltem Ballıdağ; Selami Aydın (Future in Educational Research)
Abstract Although speaking anxiety plays a significant role in English as a foreign language (EFL) learning, research indicates that English speaking anxiety stands out as a crucial problem that EFL learners experience. Integrating technology into the EFL contexts may help learners significantly, and artificial intelligence‐based (AI‐based) chatbots may create many speaking opportunities for them which can help them reduce their speaking anxiety. Nevertheless, there have been a fairly limited number of studies investigating the impact of AI‐based chatbots on reducing EFL learners' speaking anxiety. This study aims to unveil the probable effects of AI‐based chatbots on speaking anxiety. It also aims to compare traditional speaking tasks and AI‐based chatbot speaking tasks in terms of decreasing speaking anxiety. This quasi‐experimental study gathered data from 44 university preparatory students in a Turkish state university via a background questionnaire and the Turkish version of the Foreign Language Classroom Anxiety Scale. The findings demonstrated that the AI‐based chatbot speaking tasks do not significantly reduce learners' anxiety. However, traditional speaking activities with peers in the classroom significantly decrease speaking anxiety. It was recommended that teachers should not depend on AI‐based chatbots excessively by also being conscious of the potential benefits of traditional speaking tasks.